Subspecific origin and haplotype diversity in the laboratory mouse - Yang, Hyuna; Wang, Jeremy R; Didion, John P; Buus, Ryan J; Bell, Timothy A; Welsh, Catherine E; Bonhomme, François; Yu, Alex Hon-Tsen; Nachman, Michael W; Pialek, Jaroslav; Tucker, Priscilla; Boursot, Pierre; et al. (Nature genetics, 2011)
Fernando Pardo-Manuel de Villena, Gary Churchill and colleagues provide a high-resolution phylogenetic map of mouse inbred strains based on comparisons to wild-caught mice. They show that the genomes of classical strains are overwhelmingly derived from Mus musculus domesticus whereas wild-derived laboratory strains include a broad sampling of diversity from multiple subspecies with pervasive introgression. The subspecific origin, haplotype diversity and identity-by-descent map of laboratory strains can be visualized at http://msub.csbio.unc.edu/PhylogenyTool.html . Here we provide a genome-wide, high-resolution map of the phylogenetic origin of the genome of most extant laboratory mouse inbred strains. Our analysis is based on the genotypes of wild-caught mice from three subspecies of Mus musculus . We show that classical laboratory strains are derived from a few fancy mice with limited haplotype diversity. Their genomes are overwhelmingly Mus musculus domesticus in origin, and the remainder is mostly of Japanese origin. We generated genome-wide haplotype maps based on identity by descent from fancy mice and show that classical inbred strains have limited and non-randomly distributed genetic diversity. In contrast, wild-derived laboratory strains represent a broad sampling of diversity within M. musculus . Intersubspecific introgression is pervasive in these strains, and contamination by laboratory stocks has played a role in this process. The subspecific origin, haplotype diversity and identity by descent maps can be visualized using the Mouse Phylogeny Viewer (see URLs ).